การพัฒนาหลักสูตรเสริมสร้างทักษะชีวิตในยุคดิจิทัล สำหรับนักเรียนระดับชั้นมัธยมศึกษาตอนต้นของโรงเรียนสังกัดกรุงเทพมหานคร - ศิริวิศาลสุวรรณ ภรณี; นิลพันธุ์ มาเรียม; เขียววิชัย คณิต; สติมั่น อนิรุทธ์ (Journal of Research and Curriculum Development, 2020)
The purposes of this research were to 1) develop and determine efficiency of life skills enhancement curriculum in the digital age 2) study the effectiveness of life skills enhancement curriculum in the digital age. With a specific objective of 2.1) study life skills development in the digital age before, during and after using the curriculum. 2.2) study the students’ satisfaction with using the curriculum to enhance life skills in the digital age. and 3) expand the curriculum to enhance life skills in the digital age. The sample comprised 31 9th grade students during in the first semester of the academic year 2019 at Wat Bangpakok School, Ratburana District, Bangkok. The research instruments consisted of curriculum and curriculum manual for enhancing life skills in the digital age. The data was analyzed by mean, standard deviation and content analysis. The results were as follows: 1. The life skills enhancement program in the digital age for lower secondary school students in schools of the Bangkok Metropolitan Administration consisted of six elements. These are 1) principles 2) objectives 3) curriculum development stages consisting of four steps which are (1) Needs Analysis (2) Integrated to Content (3) Create Experiential Learning (4)Evaluation 5)Measurement and evaluation 6)Conditions for curriculum implementation 2.The effectiveness of the curriculum indicated that 2.1) Students have the development of life skills in the digital age at the highest level. 2.2) Students are satisfied with using the life skills enhancement curriculum in the digital age at the highest level 3. The results of the dissemination curriculum that 3.1) Students have the development of life skills in the digital age at the highest level. 2.2) Students are satisfied with the curriculum for building life skills in the digital age at the highest level.